A decision framework for comparison of coal void rehabilitation options - S Henderson; A Hocking (The Australasian Institute of Mining and Metallurgy, 2018)
Commonwealth of Australia (2016) defines rehabilitation as comprising “the design and construction of landforms as well as the establishment of sustainable ecosystems or alternative vegetation, depending upon the desired post-operational land use”. For open cut coal mines in Queensland and New South Wales, the question of how to apply this intent to pits at mine closure is repeated for hundreds of individual pits. In EISs, closure plans and public discussion, assorted treatments are proposed to rehabilitate pits. While some aspects of final voids have been intensively studied, there is little guidance on how to choose a final void treatment option that delivers the optimal outcome against rehabilitation goals. For example, in the Bowen Basin and Hunter Valley commonly proposed rehabilitation actions include reducing the angles of pit walls; however, with few voids successfully rehabilitated to date there is limited understanding of what different wall slopes will achieve.CITATION:Henderson, S and Hocking, A, 2018. A decision framework for comparison of coal void rehabilitation options, in Proceedings Life-of-Mine 2018, pp 127–130 (The Australasian Institute of Mining and Metallurgy: Melbourne).